Mechanochemical halogenation of unsymmetrically substituted azobenzenes - Barišić, Dajana; Pajić, Mario; Halasz, Ivan; Babić, Darko; Ćurić, Manda (Beilstein Journal of Organic Chemistry, 2022)
The direct and selective mechanochemical halogenation of C–H bonds in unsymmetrically substituted azobenzenes using N-halosuccinimides as the halogen source under neat grinding or liquid-assisted grinding conditions in a ball mill has been described. Depending on the azobenzene substrate used, halogenation of the C–H bonds occurs in the absence or only in the presence of PdII catalysts. Insight into the reaction dynamics and characterization of the products was achieved by in situ Raman and ex situ NMR spectroscopy and PXRD analysis. A strong influence of the different 4,4’-substituents of azobenzene on the halogenation time and mechanism was found.
Keywords: azo compounds; halogenation; mechanochemistry; N-halosuccinimide; palladium(II)

Electrophilic Aromatic Substitution - Taylor, R. (John Wiley & Sons, 1990)

Electrophilic Halogenation - De la Mare, P. B. D. (Cambridge University Press, 1976)

(untitled) - Börgel, J.; Tanwar, L.; Berger, F.; Ritter, T. (J. Am. Chem. Soc., 2018)

(untitled) - Ackermann, L. (Chem. Rev., 2011)
and references cited therein.

(untitled) - Lyons, T. W.; Sanford, M. S. (Chem. Rev., 2010)
and references cited therein.

(untitled) - Liu, X.-H.; Park, H.; Hu, J.-H.; Hu, Y.; Zhang, Q.-L.; Wang, B.-L.; Sun, B.; Yeung, K.-S.; Zhang, F.-L.; Yu, J.-Q. (J. Am. Chem. Soc., 2017)

(untitled) - Powers, D. C.; Ritter, T. (Nat. Chem., 2009)

(untitled) - Zhu, R.-Y.; Saint-Denis, T. G.; Shao, Y.; He, J.; Sieber, J. D.; Senanayake, C. H.; Yu, J.-Q. (J. Am. Chem. Soc., 2017)

(untitled) - Petrone, D. A.; Ye, J.; Lautens, M. (Chem. Rev., 2016)

(untitled) - Nattmann, L.; Saeb, R.; Nöthling, N.; Cornella, J. (Nat. Catal., 2020)

(untitled) - Ayogu, J. I.; Onoabedje, E. A. (Catal. Sci. Technol., 2019)

(untitled) - Zhai, Y.; Chen, X.; Zhou, W.; Fan, M.; Lai, Y.; Ma, D. (J. Org. Chem., 2017)

Handbook of Organopalladium Chemistry for Organic Synthesis - Hartwig, J. F. (Palladium-Catalyzed Synthesis of Aryl Ethers and Related Compounds Containing S and Se, 2002)

(untitled) - Stille, J. K. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Heck, R. F. (Synlett, 2006)

(untitled) - Suzuki, A. (Chem. Commun., 2005)

Cross-Coupling Reactions - Muci, A. R.; Buchwald, S. L. (Practical Palladium Catalysts for C-N and C-O Bond Formation, 2002)

(untitled) - Hartwig, J. F. (Synlett, 2006)

(untitled) - Hartwig, J. F. (Nature, 2008)

(untitled) - Evans, D. A.; Katz, J. L.; Peterson, G. S.; Hintermann, T. (J. Am. Chem. Soc., 2001)

U.S. Pat. Appl. - Pelletier, J. C.; Youssefyeh, R. D.; Campbell, H. F. (Substituted Saturated and Unsaturated Indole Quinoline and Benzazepine Carboxamides and Their Use as Pharmacological Agents, 1990)

(untitled) - Li, C.-J.; Trost, B. M. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Cliffe, M. J.; Mottillo, C.; Stein, R. S.; Bučar, D.-K.; Friščić, T. (Chem. Sci., 2012)

(untitled) - Juribašić Kulcsár, M.; Halasz, I.; Budimir, A.; Užarević, K.; Lukin, S.; Monas, A.; Emmerling, F.; Plavec, J.; Ćurić, M. (Inorg. Chem., 2017)

(untitled) - Monas, A.; Užarević, K.; Halasz, I.; Juribašić Kulcsár, M.; Ćurić, M. (Chem. Commun., 2016)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Porcheddu, A.; Colacino, E.; De Luca, L.; Delogu, F. (ACS Catal., 2020)
and references cited therein.

(untitled) - Schumacher, C.; Hernández, J. G.; Bolm, C. (Angew. Chem., Int. Ed., 2020)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)
and references cited therein.

(untitled) - Hernández, J. G. (Chem. – Eur. J., 2017)
and references cited therein.

(untitled) - Zhao, S.; Li, Y.; Liu, C.; Zhao, Y. (Tetrahedron Lett., 2018)

(untitled) - Howard, J. L.; Cao, Q.; Browne, D. L. (Chem. Sci., 2018)
and references cited therein.

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Pickhardt, W.; Grätz, S.; Borchardt, L. (Chem. – Eur. J., 2020)
and references cited therein.

(untitled) - Ingner, F. J. L.; Giustra, Z. X.; Novosedlik, S.; Orthaber, A.; Gates, P. J.; Dyrager, C.; Pilarski, L. T. (Green Chem., 2020)

(untitled) - Hermann, G. N.; Unruh, M. T.; Jung, S.-H.; Krings, M.; Bolm, C. (Angew. Chem., Int. Ed., 2018)

(untitled) - Cheng, H.; Hernández, J. G.; Bolm, C. (Org. Lett., 2017)

(untitled) - Cheng, H.; Hernández, J. G.; Bolm, C. (Adv. Synth. Catal., 2018)

(untitled) - Hermann, G. N.; Bolm, C. (ACS Catal., 2017)

(untitled) - Hermann, G. N.; Jung, C. L.; Bolm, C. (Green Chem., 2017)

(untitled) - Yu, J.; Yang, X.; Wu, C.; Su, W. (J. Org. Chem., 2020)

(untitled) - Rightmire, N. R.; Hanusa, T. P. (Dalton Trans., 2016)

(untitled) - Juribašić, M.; Užarević, K.; Gracin, D.; Ćurić, M. (Chem. Commun., 2014)

(untitled) - Bjelopetrović, A.; Lukin, S.; Halasz, I.; Užarević, K.; Đilović, I.; Barišić, D.; Budimir, A.; Juribašić Kulcsár, M.; Ćurić, M. (Chem. – Eur. J., 2018)

(untitled) - Bjelopetrović, A.; Robić, M.; Halasz, I.; Babić, D.; Juribašić Kulcsár, M.; Ćurić, M. (Organometallics, 2019)

(untitled) - Hernández, J. G.; Bolm, C. (Chem. Commun., 2015)

(untitled) - Ghanbari, N.; Ghafuri, H.; Esmaili Zand, H. R.; Eslami, M. (SynOpen, 2017)

(untitled) - Liu, Z.; Xu, H.; Wang, G.-W. (Beilstein J. Org. Chem., 2018)

(untitled) - Bera, S. K.; Mal, P. (J. Org. Chem., 2021)

(untitled) - Barišić, D.; Halasz, I.; Bjelopetrović, A.; Babić, D.; Ćurić, M. (Organometallics, 2022)

(untitled) - Ma, X.-T.; Tian, S.-K. (Adv. Synth. Catal., 2013)

(untitled) - Kalyani, D.; Dick, A. R.; Anani, W. Q.; Sanford, M. S. (Tetrahedron, 2006)

(untitled) - de Figueiredo, R. M.; Suppo, J.-S.; Campagne, J.-M. (Chem. Rev., 2016)

(untitled) - Xu, X.-J.; Amuti, A.; Wusiman, A. (Adv. Synth. Catal., 2020)

(untitled) - Caristi, C.; Ferlazzo, A.; Gattuso, M. (J. Chem. Soc., Perkin Trans. 1, 1984)

(untitled) - Bjelopetrović, A.; Barišić, D.; Duvnjak, Z.; Džajić, I.; Juribašić Kulcsár, M.; Halasz, I.; Martínez, M.; Budimir, A.; Babić, D.; Ćurić, M. (Inorg. Chem., 2020)